2014
DOI: 10.3892/etm.2014.1665
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diagnostic value of vWF:Ag, D-D and FDP in patients with acute cerebral infarction using ROC curves

Abstract: Cerebral infarction is usually associated with arteriosclerosis, vascular endothelial cell injury and blood flow through the vascular system. The diagnostic value of markers, including von Willebrand factor antigen (vWF:Ag), D-dimer (D-D) and fibrinogen/fibrin degradation product (FDP), have not been studied in patients with acute cerebral infarction. Thus, the aim of the present study was to use receiver operating characteristic (ROC) curves to evaluate the diagnostic significance of vWF:Ag, D-D and FDP in 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[ 37 ] D-D can be used as a sensitive indicator for the early diagnosis of cerebral infarction. [ 38 ] This study revealed that RIPostC reduced hs-CRP levels. A study also reported that RIPostC can reduce the levels of FIB and D-D.[ 27 ] Therefore, it can be speculated that RIPostC has a certain role in promoting the recovery of neurological function in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 89%
“…[ 37 ] D-D can be used as a sensitive indicator for the early diagnosis of cerebral infarction. [ 38 ] This study revealed that RIPostC reduced hs-CRP levels. A study also reported that RIPostC can reduce the levels of FIB and D-D.[ 27 ] Therefore, it can be speculated that RIPostC has a certain role in promoting the recovery of neurological function in patients with ischemic stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Another two articles were also from the same study cohort [ 29 , 31 ], and the study with smaller sample size was excluded [ 31 ]. Eventually, 10 articles [ 10 , 16 18 , 29 , 30 , 32 35 ] met the inclusion criteria and were included. Of note, although two studies were from the same study cohort [ 10 , 16 ], one study examined the risk of all types of stroke and the other examined the risk of intracerebral hemorrhage, so they were not pooled together during the analysis and were both included.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined the OR of higher D-dimer level for acute ischemic stroke [ 29 , 32 , 34 ]. The pooled OR of the three studies was 2.06 (95% CI, 1.08-3.96) (Figure 3 ), suggesting that higher D-dimer level was associated with higher risk of acute ischemic stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Rising level of D-dimer indicated the enhancement of secondary fibrinolytic activity, and can be regarded as a molecular marker of hypercoagulability and hyperfibrinolysis. [13][14][15] Zajadacz and Juszkiewicz reported that the level of D-dimer in plasma was increased, but there were two patients whose content of D-dimer was not related to the severity of disease, therefore they pointed out the possibility of coagulation disturbances in HSP with D-dimer rise (as well as decrease of plasma factor XIII and platelets described in relevant literature) should be taken into consideration. 16 Fg is a protein possessing coagulation function produced by liver, also the precursor of fibrin.…”
Section: Discussionmentioning
confidence: 99%